Pengalaman Karies Gigi pada Remaja di Nagari Koto Tangah Kabupaten Agam - Ika Ifitri; Anses Warman; Cici Idela; Alsri Windra Doni (Jurnal Sehat Mandiri, 2026)
Dental caries is the most common disease experienced by Indonesian people, especially in 12-year-olds who already have completely permanent teeth, and 12-year-old children are designated as the global monitoring age for caries. Purpose of the study to find out the description of dental caries experience in grade VII students at SMPN 1 Nagari Koto Tangah, Tilatang Kamang District, Agam Regency. A type of quantitative research with a descriptive design. The research population is all grade VII students of SMPN 1 Tilatang Kamang totaling 122 people. The sampling technique is a saturated sample, that is, the entire population is used as a sample. Data collection through direct examination. The data analysis used univariate analysis. The results of the study obtained a DMF-T index based on age, namely the bad criteria at the age of 13 years of 53%, while the DMF-T index with good criteria was also at the age of 12 years of 70%. Based on gender, the DMF-T index is 57% bad criteria for females, while the DMF-T index is good criteria for males at 70%. The average DMF-T index of 122 respondents in class VII at SMPN 1 Tilatang Kamang was 1.56 with poor criteria. The conclusion of this study is that grade VII students of SMPN 1 Tilatang Kamang have an average DMF-T index of 1.56 with poor criteria. Respondents were advised to reduce the habit of consuming sweet and sticky foods, and to apply the habit of gargling after consuming sweet and sticky foods. Filling cavities.